Metronidazole With or Without Probiotics for Prevention of Recurrent Bacterial Vaginosis: A Comparative Study - Mahaseth, Binod Kumar; Shrewastwa, Mukesh Kumar (Journal of Nepalgunj Medical College, 2025)
Introduction: Bacterial vaginosis is one of the most common vaginal infections affecting women of reproductive and also post menopausal age groups worldwide. It is characterized by a decrease in number of good bacteria like, lactobacilli and an overgrowth of pathological anaerobic bacteria, leading to symptoms such as abnormal foul smelling vaginal discharge. Till date metronidazole, ornidazole, tinidazole and clindamycin are the standard antibiotic treatment, at a same time recurrence rates have been found to be high. Probiotics have emerged as a potential adjunct therapy to restore and maintain a healthy vaginal microbiome, leads to reducing bacterial vaginosis recurrence.Aims: To evaluate the efficacy of metronidazole alone versus metronidazole added with oral probiotics in preventing bacterial vaginosis recurrence.Methods: A randomized comparative study was carried out at Nepalgunj Medical College Teaching Hospital from October 2022 to September 2023. Seventy-two non-pregnant women diagnosed with bacterial vaginosis were divided into two groups: Group A (metronidazole alone) and Group B (metronidazole with probiotics). Primary outcomes, including vaginal discharge, odor, vaginal pH, Nugent score, and bacterial vaginosis recurrence, were assessed at 8, 30, and 60 days post-treatment.Results: At the 8th day follow-up, Group B (metronidazole + probiotics) demonstrated a statistically significant reduction in abnormal vaginal discharge compared to Group A (p=0.013). By Day 60, Group B maintained superior outcomes across all measured parameters, including vaginal discharge (p=0.089), odor (p=0.230), pH (p=0.009) and Nugent scores (p